Academic Resilience and Motivation as Predictors of Academic Engagement Among Rural and Urban High School Students in Ghana - Mustapha Amoadu; John Elvis Hagan; Paul Obeng; Edmond Kwesi Agormedah; Medina Srem-Sai; Thomas Schack (Youth)
Academic resilience and motivation are two key positive psychological constructs that have the capacity to influence learners’ engagement even in difficult conditions. Surprisingly, research investigating these relational constructs is limited in Ghana. The study examined the influence of academic resilience and motivation on engagement, highlighting rural–urban variations among senior high school students. This cross-sectional survey involved 190 senior high school students in Ghana, employing stratified sampling. Academic resilience, motivation, and engagement were assessed using the academic resilience scale (ARS-30), the motivated strategies for learning questionnaire (MSLQ), and the university student engagement inventory (USEI). Data were analysed using descriptive, Pearson correlation, and hierarchical multiple regression analyses. An independent t-test was also conducted to compare the study variables between rural and urban students, utilising IBM Statistical Package for the Social Sciences (SPSS) version 27. The correlational analysis revealed that academic resilience positively correlates with engagement and motivation. A regression model indicated that socio-demographic factors have a minimal impact on academic engagement, while academic resilience and motivation significantly predict it. No significant differences were found between urban and rural students regarding academic engagement, motivation, or resilience. Educators and policymakers are urged to implement strategies, including social–emotional learning and mentorship programmes, to support and cultivate academic resilience, motivation, and engagement among students. Future studies could investigate the relationship between academic, motivational intensity, and learners’ academic achievement across a larger sample.